DESIGN OF TRANSMISSION ATTENTION SYSTEM ON AERIAL TYPE SINGLE MODE FIBER Optic Cable ON CONNECTION LOSS ON PASSIVE SPLITTER DEVICES - Aprinal Adila Asril (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2021)
In this study, several types of connections were carried out using a protection sleeve of 4 cm, 6 cm and using a barrel adapter connector and the effect of the connection on the installation of a 1:2 passive splitter device. The equipment used for the measurement process is an Optical Power Meter (OPM) and an Optical Time Domain Reflectometer (OTDR).The results of measurements using OPM at a wavelength of 1310 nm there are attenuation values with the type of connection of one connection using a protection sleeve of 4cm and 6cm, the attenuation value of the type of connection of one connection 4cm 3.908190608 dB is smaller than the type of connection of two connections 4 cm 3.930189392 dB and the value obtained is the attenuation in the connection type of one connection 6 cm 3.915557608 dB is smaller than that of the connection type two connection 6 cm 3.960067357dB. The measurement results of single mode Aerial transmission attenuation are much smaller than using Pigtail single mode cables with an attenuation value of 4 cm for one connection 4,920,818,754 dB, here there is a difference of 1.01 dB.Measurements with the OTDR produce a connection loss value for the connection type using a 6cm protection sleeve, one connection is smaller with a value of 0.155 dB, compared to the connection type using an adapter barrel with a value of 0.614 dB and the measurement results with this OTDR will also affect the total attenuation value in one transmission link. fiber optic cable. Keywords: Aerial, Singlemode, Attenuation, OPM, OTDR